For the Record: An Analysis of the Exchange of Information Between New Brunswick Long-term Care Facilities and Families During the Covid-19 Pandemic - Durkee-Lloyd, Janet; Baird, Eve; Giles, Jennie; Clowater, Brooklyn (Journal of New Brunswick Studies / Revue d’études sur le Nouveau-Brunswick, 2023)
The COVID-19 pandemic illuminated the vulnerabilities which exist within the long-term care sector. Canada, unfortunately, has the dubious distinction of having some of the highest COVID-19 long-term care facility death rates in the world. As this study purports, efficient management of a pandemic outbreak is dependent, in part, on effective communication strategies. This type of information not only transmits public health guidance but can also play a role in reducing negative social, psychological, and health impacts. The purpose of this research project was to study how individuals with a family member/sponsor living in a New Brunswick special care home or nursing home accessed information during the first and second waves of the pandemic. Participants in Survey I (n=101) conducted during the first wave and Survey II (n=110) undertaken during the second wave completed an online questionnaire about their experiences accessing information from the long-term care facility of their family member/sponsor. Participants in Survey I reported high levels of satisfaction with the adequacy of information provided; however, this declined in Survey II. Participants in Survey I reported that “great” staff and the use of technology were key to obtaining information. Participants in both surveys reported that poor-quality communication, lack of staff, and uninformed personnel were challenges to accessing the information they sought about their family member/sponsor. It was suggested by participants that regular updates, clear and concise information, and a stronger digital presence would improve communication. These findings can be useful to inform policies and procedures for communication strategies implemented in the future.